2017
DOI: 10.1155/2017/3689375
|View full text |Cite
|
Sign up to set email alerts
|

Association between Plasmatic Ceramides Profile and AST/ALT Ratio: C14:0 Ceramide as Predictor of Hepatic Steatosis in Adolescents Independently of Obesity

Abstract: Objective To assess the association between plasma ceramides and hepatic steatosis (HS) in adolescents, independently of obesity. Materials and Methods Ninety-four adolescents from two previous studies conducted and published by our crew were included. Study subjects were stratified in three groups: normal weight (n = 18), obesity (n = 34), and obesity + HS (n = 42). The presence of HS was defined when ALT/AST ratio was <1. Ceramides subspecies (C14:0, C16:0, C18:0, C24:0, and C24:1) were determined by LC/MS. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 20 publications
1
15
0
2
Order By: Relevance
“…Recent studies indicate that sphingolipids, such as SM, Cer, and S1P, play an essential role in the onset and progression of NAFLD. Cers have been shown to accumulate in the livers of NAFLD people and animals and are linked to insulin resistance and inflammation 36 . Our results confirm previous reports of Cer accumulation in HFD rats.…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies indicate that sphingolipids, such as SM, Cer, and S1P, play an essential role in the onset and progression of NAFLD. Cers have been shown to accumulate in the livers of NAFLD people and animals and are linked to insulin resistance and inflammation 36 . Our results confirm previous reports of Cer accumulation in HFD rats.…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, it was previously shown that plasmatic NEFA, TG and cholesterol were correlated to liver weight (Tavernier et al, 2017;Pioche et al, 2019). In other animal models of hepatic steatosis, lipophilic biomarkers were identified in rats (Goda et al, 2018) and specifically ceramids in mice (Dong et al, 2017) and adolescents (Maldonado-Hernández et al, 2017). Another perspective of the present study could be to search for biomarkers in the lipid fraction of the plasma.…”
Section: Conclusion -Perspectivesmentioning
confidence: 70%
“…Ceramides with C14:0, C16:0, C24:1 and C26:1 showed positive associations with changes in TG. C14:0 ceramide has been previously been implicated in nonalcoholic fatty liver disease (NAFLD) in adolescent children [35]. C16:0 ceramide inhibits mitochondrial FAO, oxidant production, and impairs Complex IV activity [25].…”
Section: Plos Onementioning
confidence: 99%